THE ROLE OF CHOLESTEROL IN ENHANCING GROWTH OF Staphylococcus aureus (Journal of Veterinary Medicine and Animal Production, 2022)
This is a prospective analytical case control study that used to assess the effect of cholesterol in enhancing growth of Staphylococcus ,the effect of different concentrations of cholesterol powder on growth of Staphylococcus and the survival of Staphylococcus in obese and non obese sera. Nutrient Agar (NA) was spread with different concentrations of cholesterol powder and cholesterol sera. Agar plates without cholesterol were prepared and used as controls. S.aureus at 10-7 cfu/ml was used at 0.25 ml to cover each plate and was spread by glass rod, then incubated aerobically at 37oC for 24 hours. Numbers of colonies on each plate were counted by digital colony counter. In this study significant differences were recorded between mean colony counts of normal cholesterol sera (non-obese sera), border line high and high cholesterol sera levels (obese sera). Also there was a significant difference between mean colony count in obese and non-obese sera levels. Significant differences were seen between mean colony counts of normal cholesterol powder, border line high cholesterol powder and high cholesterol powder Concentrations. The differences between different concentrations of cholesterol powder on the effect growth of S.aureus were found significant. The differences between mean colony counts in different levels of cholesterol sera and different concentrations of cholesterol powder were significant. A relation between the levels of serum cholesterol and the duration of growth of S. aureus was noticed. These results proved that the presence of high cholesterol levels in serum may contribute to the proliferation of S.aureus